Faktor-Faktor Yang Mempengaruhi Pencegahan Kecurangan Dengan Modal Intelektual Sebagai Variabel Mediasi - Sumarni Sumarni; Rizky Ramadhan (Fakultas Ekonomi Universitas Negeri Manado, 2024)
This research aims to analyze the relationship between individual morality, organizational culture and the whistleblowing system with intellectual capital as a mediating variable in villages in Woja District. This type of explanatory research uses a saturated sampling technique for 140 village officials, the data source uses primary data and data analysis uses the SmartPLS-SEM tool. The research show that organizational culture has a positive influence on fraud prevention, while individual morality, the whistleblowing system and intellectual capital have a negative influence on fraud prevention. The contribution of this research is regarding the importance of the village office in Woja District considering the educational background of village officials to influence the prevention of fraud because preventing fraud in the village can contribute to ensuring that village funds are right on target and are not misused, improving the welfare of village communities, preventing tendencies towards fraud.